Los microcreditos, que otorgan las instituciones financieras, a la y su percusión en la economía de las familias de la parroquia 24 Mayo del cantón Quevedo, año 2012 - Estrella Bargas, Sulin Elizabeth (2013)
The role of women in society as a cornerstone in family development in Ecuador is key, from the fact that many of them are forgers of new generations through compliant motherboard role within the family, but if we add to this business initiative we realize that the world suffers important changes that equality ever longed are catching. At present, she is not only mother and wife, but also occupies a job role. These changes have occurred that women feel more positive and strong, making a change in both labor and political spheres. Both men and women have had to adapt to these changes, changing behaviors and habits that thought they had entrenched as household chores that were exclusive to women and men were only suppliers. Share the role is part of the process; in fact today we find that parents share more with their sons / daughters, taking a closer relationship, helping the mother to share the commitments of the house in every sense of the word. Working women are, in general, trying to keep the family finances afloat, though at the cost, sometimes, of sacrificing the care of children and home. However, the rescue of them, as a light of hope has appeared microcredit, also called micro finance, which is the provision of a variety of financial services such as deposits, loans and insurance to poor families that do not have resource access formal financial institutions. The loans are used to invest in microenterprises, and to invest in health and education, improve housing or dealing with family emergencies. The typical way how microcredit is providing a small loan, the amount is determined by the borrower's repayment capacity, for a short period. Upon payment of the first loan, the borrower can opt for a second major loan, and who has learned to manage their investments and has proven to be a good player. If the recipient is eligible for promptly paying increasingly larger loans.